2021
DOI: 10.1111/wej.12740
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of a zeolite‐packed upflow baffled septic tank using tracer tests and mathematical modelling

Abstract: This work analysed the hydraulic behaviour and treatment efficiency of an upflow baffled septic tank (UBST) through tracer tests and mathematical modelling using the axial dispersion and the tank‐in‐series (TIS) models. The tracer tests were performed under different HRTs (12, 18 and 24 h) and configurations (UBST, UBST with sludge and UBST with sludge and zeolite filter). UBST followed a non‐ideal flow, and configuration modifications, rather than HRT, altered its hydraulic behaviour. Mathematical modelling i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…ii) the full scale up-flow septic tank/baffled reactor (USBR) MST, built and tested in a small town in Egypt (Sabry, 2010), with removal efficiencies of 84% COD and 89% TSS; iii) an MST followed by an up-flow AF, housed within a single cylindrical unit, designed for the in situ treatment of domestic wastewater (DWW), evaluated at laboratory scale by Sharma et al (2014), which showed removal efficiencies of 86,3±4,9% COD and 91,2±9,7% TSS; iv) an MST followed by an AF for the in situ treatment of the wastewater generated in a boarding school, with efficiencies on the order of 72,6% COD and 83,2% TSS (Sharma and Kazmi, 2015); v) an isolated AF (IAF) system incorporating a waste heat input for wastewater treatment in buildings, tested at full scale in the Phitsanulok province of northern Thailand, with removal efficiencies of 61,3% COD and 67,7% TSS (Bouted and Ratanatamskul, 2018); vi) the demonstration by Santiago-Díaz et al (2019, 2021 of the potential of decentralized wastewater management in Mexico, through the use of a UASB-septic tank strategy for the treatment of municipal wastewater, finding that this system can be built with low-cost local materials and does not require sophisticated equipment (it is also an economical alternative due to the simplicity of the technology and its easy operation); and vii) the HS comprising ST-AF, where the suspended biomass (present in the ST) is combined with adhered biomass (present in the AF) in the same reactor.…”
Section: Some Examples Of Hs Includementioning
confidence: 99%
“…ii) the full scale up-flow septic tank/baffled reactor (USBR) MST, built and tested in a small town in Egypt (Sabry, 2010), with removal efficiencies of 84% COD and 89% TSS; iii) an MST followed by an up-flow AF, housed within a single cylindrical unit, designed for the in situ treatment of domestic wastewater (DWW), evaluated at laboratory scale by Sharma et al (2014), which showed removal efficiencies of 86,3±4,9% COD and 91,2±9,7% TSS; iv) an MST followed by an AF for the in situ treatment of the wastewater generated in a boarding school, with efficiencies on the order of 72,6% COD and 83,2% TSS (Sharma and Kazmi, 2015); v) an isolated AF (IAF) system incorporating a waste heat input for wastewater treatment in buildings, tested at full scale in the Phitsanulok province of northern Thailand, with removal efficiencies of 61,3% COD and 67,7% TSS (Bouted and Ratanatamskul, 2018); vi) the demonstration by Santiago-Díaz et al (2019, 2021 of the potential of decentralized wastewater management in Mexico, through the use of a UASB-septic tank strategy for the treatment of municipal wastewater, finding that this system can be built with low-cost local materials and does not require sophisticated equipment (it is also an economical alternative due to the simplicity of the technology and its easy operation); and vii) the HS comprising ST-AF, where the suspended biomass (present in the ST) is combined with adhered biomass (present in the AF) in the same reactor.…”
Section: Some Examples Of Hs Includementioning
confidence: 99%